A Study on the Impact of Classroom Noise Suppression Designed Based on AI Speech Enhancement Technology on Teaching Effectiveness (Contemporary Education and Teaching Research, 2025)
As the digitalization of education advances rapidly, the traditional classroom knowledge-transmission mode is being phased out. The noisy classroom environment, with chaotic equipment and student chatter, reduces teachers’ voice signal clarity, distracts students, and lowers teaching efficiency and quality. This paper explores the application of AI-based speech enhancement technology in real-time classroom noise reduction. It presents a denoising system combining deep learning and multimodal signal processing, achieving real-time speech denoising in noisy settings. results show it significantly cuts noise impact, with SNR≥18db, boosts students’ class participation by 27%, and ups knowledge-point retention by 19%. Its working principle can optimize teaching and promote deep learning, offering a new acoustic solution for smart education.